Synthesis Characterization and Antibacterial, Antifungal Activity of N-(Benzyl Carbamoyl or Carbamothioyl)-2-hydroxy Substituted Benzamide and 2-Benzyl Amino-Substituted Benzoxazines. (31st October 2013) - Belz, Tyson; Ihmaid, Saleh; Al-Rawi, Jasim; Petrovski, Steve
Abstract : New N-(benzyl carbamothioyl)-2-hydroxy substituted benzamides13, 20, and21 were synthesized using sodium bicarbonate and benzyl amine with 2-thioxo-substituted-1, 3-benzoxazines6, 10a, b, 11c, and12a–n . The 2-thioxo-substituted-1, 3-oxazines6, 10a-b, 11d 12a–n, and26 were converted to the corresponding 2-methylthio-substituted-1, 3-oxazines14a–l and24 which were then converted to 2-benzyl amino-substituted-benzoxazines15a–i by refluxing with benzylamine. Products15a, b, e, f, andg were also synthesized by boiling the corresponding N-(benzyl carbamothioyl)-2-hydroxy substituted benzamides13a, b, f, l, andm in acetic acid. 2-Oxo-substituted-1, 3-benzoxazines22 and25 were prepared by treating the corresponding 2-methylthio-substituted-1, 3-oxazines14 and24 with dilute HCl. The N-(benzyl carbamoyl)-2-hydroxy substituted benzamide23 was synthesized from the reaction of 2-oxo-substituted-1, 3-benzoxazine22 with benzylamine. The new products were characterized using IR, 1 H, and 13 C NMR in addition to microanalysis. Selected compounds were tested in vitro for antibacterial and antifungi activity and the most active compounds were found to be the 4-(substituted-benzylamino)-2-hydroxy benzoic acids9a andd ( M. chlorophenolicum, MIC 50 and 25 µgm L −1, resp.), N 1, N 3-bis (benzyl carbamothioyl)-4, 6-dihydroxy-substituted phthalamides20a and20c ( B. subtilis MIC 12.5, 50 µgm L −1, resp.) and21 ( M. chlorophenolicum, MIC 50 µgm L −1 ).